(3ehGgH GdbOjQ Ydi GdLGeY GdUZjQs - (3GdCHjGQj, aGjO Hf eHGQc, (B1063 (3g`s ((3eMeO Hf GdTjN Ydi GdQaGYj GdYhVj GdTGaYjs)
(3ChdgG (B:s
(3HYO GdHSedI hGdMeOdI hHYO ajbhd GdhGKb HQHg GdYdje GdHGQj aGjO Hf eHGQc GdMfaj GdCRgQj GdGHjGQj deG Ggdfj Gddg JYGdi dCbQC GdLGeY GdUZjQ GdefShH ddLdGd GdSjhWj aj GdLGeY GdCRgQj CMHHJ Cf CMd CdaGXg HYHGQI eNJUQI hCHjf eYGfjg HJQcjH (B( (3cPG (B) (3eTJgQI hSejJg ehGgH GdbOjQ Ydi GdLGeY GdUZjQs
(3BNQgG (B:s
(3hgh ZjQ ZQGH GdRQY aGSb , hHbjI GdMOjK hGdcdH GdCShO TjWGf hgPg gj GdahGSb GdJj jMd bJdgG aj GdMd hGdMQe hcPG GdOjdej hZjQ Yf YGFTI QVj Gddg YfgG hdjcf gPG GdMQa BNQ GdLRA GdChd gh GdfUa ef ehGgH GdbOjQ Ydi GdLGeY GdUZjQs
(3efbhdI ef fSN bhHdJ Ydi fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 125s
(3eYLe GdeDdajf (B2 / 609s
(3EjVGM Gdecfhf (B2 / 602s
(3gOjI GdYGQajf (B1 / 814s
Keywords: (3GdMOjK hGdeUWdMs